Ceratopogonidae: their role in pollination and fertilization at various technological levels of Theobroma cacao L. production - Montero-Cedeño, Silvia Lorena; Cañarte-Bermudez, Ernesto Gonzalo; Navarrete-Cedeño, José Bernardo; Pinargote-Borrero , Antonio; Sanchez-Hernández, Pedro (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The goal of this study was to evaluate the role of pollinators on the pollination, fertilization and fruit set process in three technological production levels and three reproduction substrates, determinants in cocoa yield. Two pollination techniques (natural and assisted) were compared and as a control, flowers were isolated with antiaphid. Twenty-seven observation units were formed, with three biological replicates. A known number of flowers were evaluated 6, 14, 21 and 36 days after the opening of each flower on marked branches. The number of active flowers, pollinated, fertilized and fruits formed was recorded. Pollinators present in experimental units were collected using yellow sticky cards, then taken to the lab and identified. Pollination occurred up to three days after opening, the flower that remained with the ovary swollen and attached to the branch/stem was considered pollinated. Fertilization was recorded fourteen days after flower opening, fruit set begins after fertilization, an event that was quantified twenty-one days after flower opening. The systems studied did not influence the percentage of pollination, fertilization and fruit formation. However, the substrates did influence pollination, fertilization and fruit set. The assisted pollination technique is significantly superior to natural pollination. The same species of Ceratopogonidae were reported at all three levels and substrates, with genera Forcipomyia and Dasyhelea being the most abundant.